Aphasia and related neurogenic communication disorders - Papathanasiou, Ilias; Coppens, Patrick (Usa c)
"Aphasia and Related Neurogenic Communication Disorders is designed for the graduate course on Aphasia. Part 1 of the textbook covers aphasiology, while part 2 addresses related disorders. Overall, the textbook offers an overview of aphasia and related neurogenic communication disorders by presenting important recent advances and clinically relevant information. It emphasizes Evidence Based Practice by critically reviewing the pertinent literature and its relevance for best clinical practices. Case studies in all clinical chapters illustrate key topics, and a "Future Directions" section in each chapter provides insight on where the field may be headed. The WHO ICF Framework is introduced in the beginning of the text and then reinforced and infused throughout"--
Keywords: Audiology